Research on Influencing Factors of Employee Safety Behavior - Data from Construction Enterprises in Hebei Province, China - Zhao, Ang; Phakdeephirot, Nutteera (International Journal of Multidisciplinary in Management and Tourism, 2023)
The objective of this research is: (1) To identify the factors that affect employees’ safety behavior in construction enterprises; (2) To examine the relationship between organizational safety climate, psychological capital, and employees’ safety behavior in construction enterprises; (3) To construct a practical management framework to improve employees’ safety behavior in construction enterprises. In this research, with the help of colleagues, friends, and teachers, 412 employees were randomly selected from 44 enterprises with AAA credit in the Hebei construction industry to conduct an empirical investigation through an online questionnaire. Analyses data with SPSS 22.0 and AMOS 22.0 data processing tools. The results of this research are as follows: (1) From the organizational perspective, organizational safety climate is the factor that affects employees’ safety behavior in construction enterprises; From the individual perspective, psychological capital affects employees’ safety behavior in construction enterprises; (2) Organizational safety climate has a positive correlation with employees’ safety behavior in construction enterprises; organizational safety climate has a positive correlation with employees’ psychological capital in construction enterprises; employees’ psychological capital has a positive correlation with their safety behavior in construction enterprises; (3) Psychological capital plays a partial mediating role in the relationship between organizational safety climate and employees’ safety behavior in construction enterprises. Through the result analysis and discussion, this research builds a practical management framework to improve employees’ safety behavior in construction enterprises. Construction enterprises should create an excellent organizational safety climate to improve employees’ psychological capital and promote safe behavior in production activities. Moreover, to improve the safety management ability of enterprise managers in engineering projects management.